Relationship between the carbonate system and phytoplankton community in the Gulf of Guinea-Africa - Koffi, Kouakou Urbain; Konan, Estelle Severine; Hassoun, Abed EI Rahman; Kouadio, Yves (Frontiers in Marine Science, 2024)
We carried out measurements of the CO2 system parameters to evaluate the impact of carbonate and nutrients’ chemistry on phytoplankton populations in the Gulf of Guinea (GoG). The seasonal variations of the CO2 system parameters (fCO2, DIC, pH and TA) along with nitrates and phosphates were quantified weekly at surface (between 0 and 5 m depth) (5.57°N - 4.57°W) in the GoG from May to December 2020. Seawater pH varied widely during the study period, ranging between 8.10-8.35 pH units; DIC and TA varied between 1810 and 2094 μmol kg-1, and between 2051 and 2216 μmol-1 respectively. DIC peaks coincided with the high upwelling period (August and September). For phytoplankton, a total of 60 species were found belonging to four taxonomic phyla: Bacillariophyta, Dinophyta, Chlorophyta and Dictyochophyta. The highest number of phytoplanktonic species were recorded for Bacillariophyta phylum with 36 species (60%). The phylum Dinophyta comprised 22 taxa (36%) and Chlorophyta and Dictyochophyta recorded only one species (2%). The highest specific diversities were observed in August and September with 29 and 26 taxa respectively and the lowest was found in October-November (5 taxa) and December (one taxa). Bacillariophyta and Dinophyta appeared throughout the entire study period. The only species for Chlorophyta phylum appeared in June and July and the Dictyochophyta’s one in May, July and August. In general, the physical (SST, SSS) and chemical (TA, DIC, pH) parameters influenced less than 50% of the phytoplankton population in the coastal area of the GoG. Our study shows that Bacillariophyta population grows up when the physicochemical parameters’ variability increase.